A series of perylene diimide cathode interlayer materials for green solvent processing in conventional organic photovoltaics - Wolfe, Kathryn M.; Alam, Shahidul; German, Eva; Alduayji, Fahad N.; Alqurashi, Maryam; Laquai, Frédéric; Welch, Gregory C. (Beilstein Journal of Organic Chemistry, 2023)
Herein, we report on the design, synthesis, physical and chemical properties, and organic photovoltaic (OPV) device performance of four new cathode interlayer (CIL) materials based on bay N-annulated perylene diimides. Starting from the previously reported N-annulated perylene diimide (PDIN-H), the N-position was functionalized with a benzyl and pentafluorobenzyl group to make PDIN-B and PDIN-FB, respectively. Similarly, starting from the previously reported cyanated N-annulated perylene diimide (CN-PDIN-H), the N-position was functionalized with a benzyl and pentafluorobenzyl group to make CN-PDIN-B and CN-PDIN-FB, respectively. The materials exhibit solubility in the green solvent, ethyl acetate, and thus were processed into thin films using ethyl acetate as the solvent. The optoelectronic properties were assessed for both solution and film, and the electrochemical properties were probed in solution. To validate the potential as electron transporting layers, each film was used in conventional OPVs as the CIL with processing from ethyl acetate, while using a bulk heterojunction (BHJ) comprised of PM6:Y6. High power conversion efficiencies (PCEs) of 13% were achieved compared to control devices using the standard PFN-Br CIL.
Keywords: cathode interlayer materials; green solvent processing; organic photovoltaics